Numerical Simulation of the Stability of a Cutting Slope and Study on Its Reinforcement Scheme - Song Chen; Zhao Yang; Wenpeng Zhang; Liufang Li; Yibo Zheng; Ying Yuan (Advances in Civil Engineering)
Analyzing the stability of the slope and studying the reinforcement scheme can reduce ecological disasters, improve the ecological environment, and protect people’s lives and property. In this paper, taking the left side slope of ZK100 + 860∼+975 cutting of the Huizhou-Qingyuan section of the Shantou-Zhanjiang Expressway as an example, based on the strength reduction method (SRM), the stability of the slope under different conditions (natural conditions, unsupported excavation conditions, rainstorm conditions, and reinforcement conditions) is analyzed by using finite element software. The results show that the slope was almost stable before excavation, and the safety factor of slope stability decreases due to excavation, so it is in an unstable state. Rainwater has a great influence on the stability of the slope. The damage to the slope is deepened, and the stability safety factor is decreased under the rainstorm condition. The stability safety factor of the slope has increased by 24.3% after the reinforcement of the anchor rod and anchor cable, and the slope is in a stable state. It can be seen that the anchor rod and anchor cable can effectively control the deformation of the slope and have a good reinforcement effect.